Analysis of Outpatient Satisfaction with Health Personnel Services at the Haji General Hospital Medan - Wahyuni, Yuyun; Ismah, Zata; Agustina, Dewi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2024)
Low quality healthcare services result in an increase in the number of deaths each year, with an estimated 5.7 to 8.4 million people dying in low and middle-income countries. This figure represents about 15% of total deaths in those countries. The impacts of inadequate services encompass a decrease in societal productivity and potential economic losses for the country of approximately 1.4 to 1.6 trillion annually.The aim of this research is to identify the relationship between the quality of services provided by healthcare professionals and the level of patient satisfaction among outpatient care recipients at Haji Medan General Hospital. The studied population includes all outpatient care patients currently receiving treatment, with a sample size of 120 individuals, selected using the Accidental Sampling method. The research method employed is a quantitative approach with a Cross-Sectional design.Research findings reveal that out of the 120 respondents, there is a relationship between independent variables such as reliability (x1), responsiveness (x2), assurance (x3), empathy (x4), as well as physical evidence (x5), and the dependent variable, which is the level of patient satisfaction (y) among those receiving outpatient care at Haji Medan General Hospital, with a p-value less than 0.05.In analyzing patient satisfaction levels, around 66% of the total 120 respondents expressed dissatisfaction with the healthcare services at Haji Medan General Hospital. Independent variables that exhibit a strong correlation with the dependent variable include reliability, responsiveness, assurance, patient satisfaction level, physical evidence, and empathy. Based on these findings, it can be concluded that there is a relationship between the quality of services provided by healthcare professionals and the level of patient satisfaction at the hospital.